A hybrid multi–criteria decision support system for selection of optimum fuel blend. (16th July 2013) - Sakthivel, G.; Nagarajan, G.; Ilangkumaran, M.; Kumar, S Sathish; Suresh, K.S.
The increasing diesel consumption, depletion of fossil fuels and environmental concerns have prompted usage of biodiesel. The selection of appropriate source and blending of biodiesel plays a role in alternate energy production. The aim of this study is to evaluate the optimum blend using Multi Criteria Decision Making (MCDM) technique. Five alternative fuel blends are prepared by varying the amount of DEE in fish oil biodiesel. Brake thermal efficiency, exhaust gas temperature, oxides of nitrogen, smoke, hydrocarbon, carbon monoxide, carbon dioxide are considered as evaluation criteria. A single cylinder direct injection diesel engine was used. Two MCDM techniques, Fuzzy Analytical Hierarchy Process (FAHP) and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) are integrated and proposed as Hybrid MCDM model to obtain the optimum blend. The exergy performance parameters were calculated for diesel and biodiesel blends, and found that the tested biodiesel offer similar performance as diesel fuel.